Новый эпиграфический памятник из Неаполя Скифского (предварительная публикация) - Виноградов, Ю.Г.; Зайцев, Ю.П. (Археологія, 2003)
В статье в предварительном варианте рассмотрена уникальная стихотворная эпитафия из Неаполя Скифского. У 1999 р. під час розкопок південно-західної частини Південного палацу Неаполя Скіфського було знайдено численні уламки вапнякової плити з восьмирядковим давньогрецьким написом. Розмір відновленої частини плити 78 х 64 см. Вона має архітектурне оформлення і рельєфні зображення. Найбільший інтерес становить віршований напис. Хоча він погано зберігся, але дає цікаву інформацію про багатославного царя Аргота та інші дані, за допомогою яких проведено історичну реконструкцію взаємозв'язків скіфів із Боспорським царством за часів правління Скілура. Розглянуто ситуаційні обставини спорудження мавзолею Аргота у Неаполі Скіфському. In 1999 during the excavations of the south-western part of the Southern palace of Scythian Naples it was found the number of debris of the lime slab with Greek octave. The dimensions of the restoring part of the slab is 78 x 64 sm. It has architectural decoration and embossed portrayal. The most interest arouses octave. In spite of its bad condition it gives the interesting information about famous chieftain Argont and other data, which helps to make the historical reconstruction of interrelations between Scythian and Kingdom of the Bosporus during the Scilur’s rein. It was reviewed circumstances of Argot’s mausoleum construction in Scythian Naples.